Primary prevention of cardiovascular disease in patients with systemic lupus erythematosus: case series and literature review. (December 2017) - Fasano, S; Margiotta, D P; Navarini, L; Pierro, L; Pantano, I; Riccardi, A; Afeltra, A; Valentini, G
Background: Systemic lupus erythematosus is associated with an increased risk of cardiovascular disease. Low-dose aspirin, hydroxychloroquine and statins have been suggested to play a prophylactic role of cardiovascular events. This study is devoted to reviewing the literature on the topic and assessing the effects of these drugs in preventing a first cardiovascular event in a two-centre Italian series. Methods: A PubMed search on cardiovascular prevention in systemic lupus erythematosus was performed. Moreover, systemic lupus erythematosus patients admitted to two centres from 2000–2015, who at admission had not experienced any cardiovascular event, were investigated. Aspirin, hydroxychloroquine and statin use, and the occurrence of any cardiovascular event, were recorded at each visit. Kaplan-Meier and Cox regression analyses were performed to evaluate the role of traditional, disease-related cardiovascular risk factors and of each of the three drugs in the occurrence of new cardiovascular events. Results: The literature search produced conflicting results. Two hundred and ninety-one systemic lupus erythematosus patients were included in the study and followed for a median of eight years. During follow-up, 16 cardiovascular events occurred. At multivariate analysis, taking aspirin (hazard ratio: 0.24) and hydroxychloroquine for more than five years (hazard ratio: 0.27) reduced, while antiphospholipid antibody positivity (hazard ratio: 4.32) increased, the risk of a first cardiovascular event. No effect of statins emerged. Conclusion: Our study confirms an additive role of aspirin and hydroxychloroquine in the primary prophylaxis of cardiovascular events in Italian patients with systemic lupus erythematosus. The lack of any detected effect in previous reports may depend on the design of studies and their short follow-up period.